Alternativa Metodológica Para El Desarrollo De La Competencia Comunicativa Oral En Idioma Inglés - Sandra Liliana Abarca García; Maritza Lucìa Larrea Vejar; Sandra Leticia Guijarro Paguay (European Scientific Journal, ESJ, 2018)
The objective of this research, was to develop an alternative as a methodological proposal to improve the oral communicative competence in the English language, as it could determine that students do not have an adequate development of the understanding, interpretation, and recognition of vocabulary. The research is descriptive. Deductive, bibliographic and documentary methods were used. The research technique for the collection of the information was the survey while the instrument was a questionnaire validated and verified by academic peers. The research sample was intentional and represented by 20 specialists in the area of English knowledge from different institutions of higher education. The development of the proposal was made on the basis of literature review with emphasis on theoretical foundation, objectives, requirements, features, and structuring. The proposal was systematic and structured in stages, which considered objectives, actions and methodological guidance. The instrument allowed to evaluate the alternative proposal in the context of the investigation. The data obtained were tabulated, analyzed and interpreted, and represented with, charts and statistics graphics.The majority of the experts concluded, that it is adequate, structured, and it can be implemented as a methodological alternative to improve the oral communicative competence.